Prevalence and risk factors associated with Clonorchis sinensis infections in rural communities in northern Vietnam. - Thao T B Nguyen; Veronique Dermauw; Hafid Dahma; Dung Thi Bui; Trang T H Le; Ngan T T Phi; Laetitia Lempereur; Bertrand Losson; Olivier Vandenberg; Dung Trung Do; Pierre Dorny (Public Library of Science (PLoS), 2020)
Background Clonorchiasis, caused by the fish-borne trematode Clonorchis sinensis, is a neglected tropical disease and a public health issue in endemic countries. In Vietnam, an in-depth analysis of risk factors for the condition is missing up to now. This study aimed to determine the prevalence of C. sinensis infection and associated risk factors in rural communities in northern Vietnam. Methodology/principal findings A cross-sectional survey was conducted in 4 communes in Yen Bai and Thanh Hoa provinces where clonorchiasis is known to be present and raw fish consumption is a common. Using a simple random sampling approach, stool was collected from 841 participants over 6 years old for coprological examination, and a questionnaire measured knowledge, attitudes, and practices with regard to clonorchiasis in 757 participants over 15 years old. Univariable and multivariable logistic regression models were run to identify risk factors for infection with C. sinensis. The overall prevalence of C. sinensis infection was 40.4%, with commune prevalences ranging between 26.5% and 53.3%. In the final model, males were significantly more likely to be infected with C. sinensis (OR 2.00; 95% CI 1.31-3.05). Recent (i.e. last year) consumption of raw fish (OR 8.00, 95% CI 4.78-13.36), low education level (OR 5.57; 95% CI 2.37-13.07), lack of treatment (OR 1.82, 95% CI 1.15-2.89), being between 19 to 39 years old (OR 6.46; 95% CI 1.25-33.37), and the presence of an unhygienic toilet (OR 2.74, 95% CI 1.53-4.92) were significantly associated with C. sinensis infection. Conclusion/significance This study demonstrated a high prevalence of C. sinensis infection in rural communities in northern Vietnam. Thus, control measures including, mass drug administration for those communes should be applied to reduce the prevalence. Moreover, specific health education activities should be developed for risk groups in C. sinensis endemic areas.